Effectiveness of Cassava Leaves Extract (Manihot esculenta Crantz) on the Number of Osteoblast and Osteoclast of Periodontitis Rat Model - Amandia Dewi Permana Shita; Zahara Meilawaty; Agustin Wulan Suci Dharmayanti; Amelia Nur Ilahi; Octaviana Putri Puspita Sari (Health Notions, 2022)
Periodontitis is a disease of periodontal tissue, one of which is caused by Porphyromonas gingivalis (P.gingivalis). P.gingivalis causes alveolar bone destruction by triggering macrophages and PMNs to release proinflammatory cytokines. Osteoblasts and osteoclasts play a role in alveolar bone remodeling. Decreased osteoblasts and increased osteoclasts resulted in the inhibited remodeling process. Periodontitis can be slowed down with cassava leaves. The purpose of this study was to examine the effectiveness of cassava leaves on the number of osteoblasts and osteoclasts in a rat model of periodontitis. This research is an experimental laboratory with a post-test-only control group design. The samples were male Wistar rats which were divided into (1) control (K) and (2) treatment induced by P.gingivalis. the treatment group was divided into aquadest (P1), metronidazole (P2), and cassava leaves (P3). Euthanasia was performed for the preparation of histopathological preparations with Hematoxylin Eosin (HE) staining. Observations with a microscope magnification 400x. The results of the calculation of the number of osteoblasts and osteoclasts between groups of cassava leaves and metronidazole were almost the same, so it was said that cassava leaves were effective in increasing the number of osteoblasts and reducing the number of osteoclasts in a rat model of periodontitis.Keywords: osteoblasts; osteoclast;  periodontitis; metronidazole; cassava leaves